CPE OF URANIUM (VI) USING IONIC LIQUID - SANAA NAÏT-TAHAR; MOHAMED A. DIDI; DIDIER VILLEMIN (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Cloud point extraction (CPE) was used to extract uranium (VI) from an aqueous solution in acetate media. The methodology used is based on the formation of uranyl-ionic liquid (I) complexes and uranyl-D2EHPA soluble in a micellar phase of non-ionic surfactant (Triton X-100). The uranium (VI) complexes are then extracted into the surfactant-rich phase at ambient temperature. The ionic liquid (IL) used as a chelating agent was synthesized and characterized in this study. It is composed of N-butyl N’-triethoxy methyl imidazolium cation and diethylhexylphosphate (D2EHPA-H) as anion. The effect of the IL on the extraction efficiency was studied in presence and in absence of IL’s cation in acetate medium.